Internalisasi nilai keluarga dan regulasi emosi: Dapatkah membentuk perilaku sosial remaja? - Josua, Dian Pertiwi; Sunarti, Euis; Krisnatuti, Diah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThe study of the condition of the area of residence, internalization of family values, and emotional regulation, of adolescent social behavior, is important because the environment influences feelings, and as a motive for adolescent behavior. This study aims to look at the influence of the environment, internalization of family values , and emotional regulation on adolescent social behavior. The study was conducted in five schools in the Districts of Abadijaya and Mekarjaya, Depok City. The study participants consisted of 120 adolescents (men n = 60 & women n = 60) and 120 working mothers taken using disproportional random sampling techniques. Data collection using the Asian Value Scale-Revised (AVS-R), Cognitive Emotional Regulation Questionnaire (CERQ), and Maladaptive Social Behavior. The PLS analysis results show that there are effects of environmental characteristics, family characteristics, internalization of family values, and emotional regulation on adolescent social behavior.Keywords: Adolescent emotional regulation; Adolescent social behavior; Family values Residential environment AbstrakStudi tentang kondisi wilayah tempat tinggal, internalisasi nilai-nilai keluarga, dan pengaturan emosi, terhadap perilaku sosial remaja penting dilakukan karena lingkungan berpengaruh terhadap perasaan, dan sebagai motif perilaku remaja. Penelitian ini bertujuan untuk melihatan pengaruh lingkungan, internaliasi nilai keluarga dan regulasi emosi terhadap perilaku sosial remaja. Penelitian dilakukan di lima sekolah yang ada di Kecamatan Abadijaya dan Mekarjaya Kota Depok. Partisipan penelitian terdiri dari 120 remaja (laki-laki n=60 & perempuan n=60 dan 120 ibu bekerja yang diambil menggunakan teknik disproportional random sampling. Pengumpulan data menggunakan skala Asian Value Scale Revisied (AVS-R), Cognitive Emotional Regulation Questionnaire (CERQ) dan Maladaptive Social Behaviour. Hasil uji PLS menunjukkan terdapat pengaruh karakteristik lingkungan, karakteristik keluarga, internalisasi nilai keluarga, dan regulasi emosi terhadap perilaku sosial remaja. Kata kunci: lingkungan tempat tinggal; nilai keluarga; pengaturan emosi remaja; perilaku sosial remaja